Pengaruh Literasi Keuangan Terhadap Perilaku Fear Of Missing Out (FOMO) dalam Pengelolaan Keuangan Pribadi pada Generasi-Z di Kota Bandung - Fanica Salwa Risqina; Vina Anggilia Puspita (Jurnal Akuntansi, Ekonomi dan Manajemen Bisnis, 2025)
This study aims to analyze the effect of financial literacy on Fear of Missing Out (FOMO) behaviour in personal financial management among Generation-Z in Bandung City. A quantitative research method was employed using a survey approach, with data collection online through questionaires distributed to 108 Generation-Z respondents via the Google Forms platform. The data were analyzed using simple linear regression with the assistance of IBM SPSS 27 software. The results indicate that financial literacy has a positive and significant influence on Fear od Missing Out (FOMO) behaviour, as indicated by a t-value of 10.198, which exceeds the critical value of 1.982, and a significance level of 0.000 (<0.05). These findings suggest that individual’s with higher financial literacy tend to experience stronger of Fear of Missing Out (FOMO) behaviour. Therefore, financial knowledge alone is not sufficient to prevent impulsive financial behaviour. A more comprehensive approach is needed, including the practical applicaton of financial literacy in daily financial decision-making. Additionally, the development of healthy financial attitudes and the strengthening of self-control skills are essential so that individuals can face social pressures and consumerist temptations more wisely, and make financial decisions not merely based on social influence or current trends.